Electronically Tunable Multi-Terminal Floating Nullor and Its Applications - Tangsrirat, Worapong (Společnost pro radioelektronické inženýrství, 2008)
A realization scheme of an electronically tun- able multi-terminal floating nullor (ET-MTFN) is de- scribed in this paper. The proposed circuit mainly employs a transconductance amplifier, an improved translinear cell, two complementary current mirrors with variable current gain and improved Wilson current mirrors, which provide an electronic tuning of the current gain. The va- lidity of the performance of the scheme is verified through PSPICE simulation results. Example applications employing the proposed ET-MTFN as an active element demonstrate that the circuit properties can be varied by electronic means.
Keywords: Four-Terminal Floating Nullor (FTFN); Current Conveyor (CC); current-mode circuits